Radiological and clinical difficulties in the management of chronic maxillary sinusitis in β Thalassemic paediatric patients. (May 2016) - Di Mauro, R.; Greco, L.; Melis, M.; Manenti, G.; Floris, R.; Giacomini, P.G.; Di Girolamo, M.; Di Girolamo, S.
Abstract: Introduction: Beta thalassemia is a blood dyscrasia that caused a marked expansion of active marrow spaces and extramedullary haematopoiesis results. In these patients various alterations and abnormalities affects different body areas, including increased risk of sinusitis. The marrow expansion in the facial bones results in delay in pneumatisation of the sinuses, overgrowth of the maxillae, and forward displacement of the upper incisors with skeletal deformities. In current literature, maxillary sinuses are not deeply evaluated by CT scan studies in these kind of patients. The aim of our study was to investigate the presence of maxillary sinuses abnormalities by the use of CT in patients with beta-thalassemia major and to compare these findings with a control group free from this disease. Materials and methods: A retrospective analysis of 22 paediatric patients with beta-thalassemia major and 22 control subjects without sinonasal diseases was performed. CT was done using a 64-multidetector-row CT scanner without contrast injection, obtained in axial plane using thin-slice technique. Evaluated parameters were: bone thickness of the lateral and anterior wall, density and volume of the maxillary sinuses. Results: Significant difference was found between the study group and control group in the evaluation of all the parameters examined. The maxillary sinus of β thalassemic patients was smaller respect of controls, the bone was more dense and thick in the side and anterior wall. Beta-thalassemic patients have a relative risk of 2.87 to develop a maxillary sinusitis. Discussion: In these patients there is an increased incidence of sinonasal infections due to the abnormal development of cranio facial skeleton. These bone alterations might confuse the physicians and lead to an increased rate of sinusitis diagnoses.